ANALISIS PENERAPAN ETIKA BISNIS ISLAM DAN URGENSINYA PADA UNIT-UNIT USAHA ORGANISASI KEMASYARAKATAN - Nurvajri TR, Cut (Prodi Hukum Ekonomi Syariah, STI Syariah AL-Hilal SIgli, 2025)
The purpose of this writing is to provide analytical results related to the application of Islamic business ethics and its urgency in community organization business units. The research method used in this writing adopts a qualitative research method. The writing of this journal uses a literature review approach through several valid sources. The results of the research conducted are that community organizations have a role in the spiritual, economic, and social fields of society. Several community empowerment activities and social activities are supported by several mass organizations in managing the business units they run. Islamic business ethics include honesty, social responsibility, transparency, prohibition of usury, and having a fair attitude. The conclusion drawn from this study is that community organizations that implement sustainably can become pioneers in reviving a sharia-based economy. The urgency of Islamic business ethics in community organization business units includes becoming a role model in the sharia economy, increasing the competitiveness of community organization business units, realizing a just people's economy, preventing unethical business practices, and increasing public trust.